2010
DOI: 10.3109/01676830903324268
|View full text |Cite
|
Sign up to set email alerts
|

Transcutaneous Dysport Injection for Treatment of Upper Eyelid Retraction Associated with Thyroid Eye Disease

Abstract: A single transcutaneous injection of Dysport is safe and effective for treatment of lid retraction due to TED. Minor complications such as ptosis and diplopia may occur, however, this modality may offer temporary relief for patients with dysthyroid lid retraction awaiting orbital decompression or strabismus surgery or both.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
25
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(29 citation statements)
references
References 17 publications
4
25
0
Order By: Relevance
“…The effect of BTX-A remained for (19.00 ± 1.71 weeks) by a single session. This matches with Ozkat and colleagues, 12 Shih and colleagues, 14 Costa and colleagues, 15 and Salour and colleagues 6 but does not match with Uddin and Davies 9 as their patients received multiple injections.…”
Section: Discussionsupporting
confidence: 66%
See 2 more Smart Citations
“…The effect of BTX-A remained for (19.00 ± 1.71 weeks) by a single session. This matches with Ozkat and colleagues, 12 Shih and colleagues, 14 Costa and colleagues, 15 and Salour and colleagues 6 but does not match with Uddin and Davies 9 as their patients received multiple injections.…”
Section: Discussionsupporting
confidence: 66%
“…With regard to the BTX-A group, our result matches with several studies. 4,6,9,1215 We had complications in the form of ptosis and ecchymosis which have been reported in some studies. Other complications as diplopia and ocular mobility affection have been reported by Uddin and Davies.…”
Section: Discussionmentioning
confidence: 75%
See 1 more Smart Citation
“…When injected via a transcutaneous approach, Btx-A can achieve similar lid lowering effects with good safety and efficacy 34,35,37,39 . In addition, the study by Costa et al found the lid lowering effects of Btx-A lasted longer in patients with fibrotic-stage TED as compared to patients with congestive-stage TED 40 .…”
Section: Induce Ptosis/reduce Lid Retractionmentioning
confidence: 99%
“…Temporary improvement of the palpebral fissure height has been observed with doses of 2.5-10 U Botox delivered by transconjunctival injection just above the upper tarsal border into the levator-Müller muscle complex. 87,88,89 Salour et al 90 reported that a single dose of 20 U of Dysport injected transcutaneously at the central superior tarsal border into the levator aponeurosis and Müller muscle was a safe and effective treatment. Ptosis and diplopia may arise as minor complications.…”
Section: Introductionmentioning
confidence: 99%